Using Body Maps to Understand Elementary Teacher Candidates' Embodied Understanding of Care Related to Intersectional Marginalization during the COVID-19 Pandemic. (2nd January 2023) - Maddamsetti, Jihea
ABSTRACT: Teacher educators need to thoroughly understand of teacher candidates' (TCs) experiences during the COVID-19 pandemic, in order to support TCs' development and practice of care in the post-pandemic era. Here, I examine how TCs identified body discourses, and examine how those TCs understood and enacted critically oriented caring practices during the pandemic in online asynchronous courses in the Southeastern U.S. I used body mapping as a pedagogical tool for TCs to identify, critically reflect on, and respond to body discourses that emerged during the COVID-19 pandemic in their process of understanding and enacting caring practices. I find that TCs conceptualized their care toward students, families, and colleagues in three overlapping yet distinct ways: (a) care as a motherly presence; (b) care as relational work; and (c) care as the promotion of critical consciousness. This study contributes to current teacher education scholarship by showing that a deeper understanding of TC's embodied experiences is critical for supporting TCs' understanding and practice of care. In addition, this work highlights how body mapping activities can be used in practice, in order to scaffold teachers' critically oriented care work.